EARNINGS QUALITY: PRAKTIK DAN TELAAH KASUS GARUDA INDONESIA - Bhakti Utami, Rachma; Ary Kartikasari, Dinar (Profit: Jurnal Adminsitrasi Bisnis, 2021)
Earnings are the critical indicators of a company's financial performance. Investors' investment decisions can be taken, predicting the company's future growth, and even earnings can determine the unsteady in an institution's stock price. Earning quality in a company's financial reporting is a must because quality earnings are real earnings without earnings management. In 2019, the financial statements of Garuda Indonesia (GI) were quite crowded and caused polemics. The airline with the GIAA issuer code managed to record a net profit of US $809 thousand in 2018, inversely proportional to the financial statements of 2017, which lost US$ 216.58 million. This performance is quite surprising because, in the third quarter of 2018, the company still lost US$ 114.08 million. Otoritas Jasa Keuangan (OJK) also investigated this case until finally, in mid-June 2019, OJK imposed sanctions on the Office of Public Accountants that audited financial statements and imposed fines on Directors of Garuda Indonesia. This case is reminiscent of the importance of applying earnings quality to reporting a company's financial statement.